An Experimental Approach to Transdisciplinary Methodology in Housing: A Transdisciplinary Approach in Housing - Özdamar, Esen Gökçe (Enquiry The ARCC Journal for Architectural Research, 2021)
This article explores a transdisciplinary research method derived from the need to determine the tacit knowledge in the re-reading of contemporary housing patterns in Narcity in Istanbul, Donau City in Vienna, and the Eastern Docklands in Amsterdam. The need for the development of such a method derives from two main problems: first, the necessity of re-reading the new dynamics of contemporary housing within the context of changing urban narratives in a globalised world; second, the consideration of the need for a dynamic view that engages both the subject and object in housing research. The residential areas are simultaneously evaluated at three levels defined by Basarab Nicolescu through an experimental and three-dimensional surface and inquiry space. It is projected that this methodology can help transgress the boundaries between fixed forms of policies and production and help bridge fact and fiction in re-reading and mapping controversies among researchers at different levels of comprehension.